Income business cycles - Geraldine Dany-Knedlik; Alexander Kriwoluzky; Sandra Pasch (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Using a wide variety of business cycle dating and filtering techniques, this paper documents the cyclical behavior of the post-tax income distribution in the US. First, all incomes are cyclical and co-move with the business cycle. Second, lower and higher income individuals experience significantly larger fluctuations across the business cycle than middle-income individuals. Third, these fluctuations have become smaller over the course of the Great Moderation for the bottom and the very top income individuals. With the financial crisis starting in 2009 and its repercussions, the volatilities are again increasing; however, not significantly. These findings are independent from the method to extract the business cycle component.
Keywords: E01; E32; D31; 330; cyclicity of the income distribution; business cycle